Pengaruh Promosi Media Sosial, Suasana Toko dan Budaya Konsumen Terhadap Keputusan Pembelian Konsumen Kafe di Lombok Timur - Pirna Saputri; Handry Sudiartha Athar; Lalu Adi Permadi (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2023)
This study aims to determine the effect of social media promotion (X1), store atmosphere (X2), and consumer culture (X3) on purchasing decisions of cafe consumers in East Lombok. Respondents in this study amounted to 110 consumers. The type of research used is associative research with a quantitative approach. The data collection method uses a survey through a questionnaire. The analysis technique used is Multiple Linear Regression using SPSS version 26.0. The results of this study indicate that: (1) Social Media Promotion has no significant effect on the Purchase Decision of Cafe Consumers in East Lombok. (2) Shop Atmosphere has a positive and significant effect on Purchase Decisions of Cafe Consumers in East Lombok. (3) Consumer culture has a positive and significant effect on purchasing decisions of cafe consumers in East Lombok